2015
DOI: 10.7554/elife.09343
|View full text |Cite
|
Sign up to set email alerts
|

Stress induced gene expression drives transient DNA methylation changes at adjacent repetitive elements

Abstract: Cytosine DNA methylation (mC) is a genome modification that can regulate the expression of coding and non-coding genetic elements. However, little is known about the involvement of mC in response to environmental cues. Using whole genome bisulfite sequencing to assess the spatio-temporal dynamics of mC in rice grown under phosphate starvation and recovery conditions, we identified widespread phosphate starvation-induced changes in mC, preferentially localized in transposable elements (TEs) close to highly indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
290
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(319 citation statements)
references
References 81 publications
27
290
2
Order By: Relevance
“…In rice, it has been reported that the most predominant mechanism of LP-induced differential methylation is the methylation of TEs triggered by changes in the expression of PSR genes (42). Although we also observed this phenomenon in Arabidopsis, we found that the methylation of TEs in close proximity to PSR genes was significantly reduced in comparison with cases in which differential methylation in gene bodies or upstream regions was associated with PSR genes.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In rice, it has been reported that the most predominant mechanism of LP-induced differential methylation is the methylation of TEs triggered by changes in the expression of PSR genes (42). Although we also observed this phenomenon in Arabidopsis, we found that the methylation of TEs in close proximity to PSR genes was significantly reduced in comparison with cases in which differential methylation in gene bodies or upstream regions was associated with PSR genes.…”
Section: Discussioncontrasting
confidence: 51%
“…These results suggested the presence of an alternative route of methylation affecting gene expression, such as the positive modulation of transcription via DNA methylation of gene bodies in which methylation acts as a mark for binding specific methylationassociated proteins. Additionally, differential methylation in repetitive elements may result from changes in methylation triggered by the activation or repression of PSR in neighboring genes, as recently reported in rice (42).…”
Section: Discussionmentioning
confidence: 98%
“…For RNA-seq studies, sample preparation and transcript analysis were performed as previously described (Secco et al, 2015), with several exceptions. First, samples were harvested 30 min, 1 h, 3 h, or 24 h after transfer to fresh medium (from low Pi to low Pi, high Pi to high Pi, or low Pi to high Pi).…”
Section: Transcript Analysismentioning
confidence: 99%
“…This elevation of mCHH in regions surrounding genes is much less prevalent in Arabidopsis (10). A recent study showed that high mCHH can also be induced near genes that are up-regulated in plants subjected to phosphate starvation (15).…”
mentioning
confidence: 99%